STUDI LITERATUR: PERANAN PENGGUNAAN MODEL-MODEL PEMBELAJARAN PADA MATERI INTEGRAL - Ayu Rahayu; Suryadi Ishak (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
This article presents a literature review on various learning models applied to improve mathematics learning outcomes in integral calculus. The 4 studies that form the basis of the literature study have discussions in understanding integral concepts, critical thinking skills, motivation and learning outcomes and the dimensions of character education. These four studies provide a comprehensive picture of the various approaches that can be used to improve students' understanding and learning outcomes in integral calculus. The first study highlights the effectiveness of the Problem-Based Learning (PBL) model in enhancing students' understanding of integral concepts. The PBL model has been shown to encourage active student engagement and sharpen critical thinking skills. The second study compares two learning models, Discovery Learning and Accelerated Learning, focusing on students' learning motivation and mathematics learning outcomes in integral calculus. The results indicate that Discovery Learning is more effective in improving students' motivation and their deeper understanding of integral concepts. The third study implements Lesson study with a PBL approach that incorporates character education in the class. This approach not only improves mathematical understanding but also develops students' character, such as collaboration and curiosity. Meanwhile, the fourth study develops a learning device for integral calculus based on a problem-solving model to enhance students' creative thinking abilities. These four studies demonstrate that problem-based learning models, whether PBL, Discovery Learning, or problem-solving-based instructional devices, are effective in improving students' understanding and critical thinking skills in integral calculus.